Preparing for a Foreign Animal Disease Outbreak Using a Novel Tabletop Exercise - Linskens, Eric J.; Neu, Abby E.; Walz, Emily J.; St. Charles, Kaitlyn M.; Culhane, Marie R.; Ssematimba, Amos; Goldsmith, Timothy J.; Halvorson, David A.; Cardona, Carol J. (Prehospital and disaster medicine, 2018)
IntroductionForeign animal disease (FAD) outbreaks can have devastating impacts, but they occur infrequently in any specific sector anywhere in the United States (US). Training to proactively discuss implementation of control and prevention strategies are beneficial in that they provide stakeholders with the practical information and educational experience they will need to respond effectively to an FAD. Such proactive approaches are the mission of the Secure Food System (SFS; University of Minnesota; St. Paul, Minnesota USA). The SFS exercises were designed as educational activities based on avian influenza (AI) outbreaks in commercial poultry scenarios. These scenarios were created by subject matter experts and were based on epidemiology reports, risk pathway analyses, local industry practices, and site-specific circumstances. Target audiences of an exercise were the groups involved in FAD control: animal agriculture industry members; animal health regulators; and diagnosticians. Groups of industry participants seated together at tables represented fictional poultry premises and were guided by a moderator to respond to an on-farm situation within a simulated outbreak. The impact of SFS exercises was evaluated through interviews with randomized industry participants and selected table moderators. Descriptive statistics and qualitative analyses were performed on interview feedback. Eleven SFS exercises occurred from December 2016 through October 2017 in multiple regions of the US. Exercises were conducted as company-wide, state-wide, or regional trainings. Nine were based on highly pathogenic avian influenza (HPAI) outbreaks and two focused on outbreaks of co-circulating HPAI and low pathogenicity avian influenza (LPAI). Poultry industry participants interviewed generally found attending an SFS exercise to be useful. The most commonly identified benefits of participation were its value to people without prior outbreak experience and knowledge gained about Continuity of Business (COB)-permitted movement. After completing an exercise, most participants evaluated their preparedness to respond to an outbreak as somewhat to very ready, and more than one-half reported their respective company or farms had discussions or changed actions due to participation. Evaluation feedback suggests the SFS exercises were an effective training method to supplement preparedness efforts for an AI outbreak. The concept of using multi-faceted scenarios and multiple education strategies during a tabletop exercise may be translatable to other emergency preparedness needs. LinskensEJ, NeuAE, WalzEJ, St. CharlesKM, CulhaneMR, SsematimbaA, GoldsmithTJ, HalvorsonDA, CardonaCJ. Preparing for a foreign animal disease outbreak using a novel tabletop exercise. Prehosp Disaster Med. 2018;33(6):640-646.